2022
DOI: 10.1183/16000617.0028-2022
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols, flavonoids and inflammasomes: the role of cigarette smoke in COPD

Abstract: COPD is predicted to become the third leading cause of morbidity and mortality worldwide by 2030. Cigarette smoking (active or passive) is one of its chief causes, with about 20% of cigarette smokers developing COPD from cigarette smoke (CS)-induced irreversible damage and sustained inflammation of the airway epithelium. Inflammasome activation leads to the cleavage of pro-interleukin (IL)-1β and pro-IL-18, along with the release of pro-inflammatory cytokines via gasdermin D N-terminal fragment membrane pores,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 187 publications
1
4
0
Order By: Relevance
“…It is reported that budesonide can limit the excessive stimulation of immune cells, as well as the release of inflammatory cytokines 35 . N‐Acetylcysteine has shown the potential to improve the immune state of patients by downregulating pro‐inflammatory through modulating and suppressing the NLRP3 inflammasome pathways of macrophages 36 . Our present results also determined the regulatory role of budesonide and N‐acetylcysteine in the immune function of MP infection.…”
Section: Discussionsupporting
confidence: 66%
“…It is reported that budesonide can limit the excessive stimulation of immune cells, as well as the release of inflammatory cytokines 35 . N‐Acetylcysteine has shown the potential to improve the immune state of patients by downregulating pro‐inflammatory through modulating and suppressing the NLRP3 inflammasome pathways of macrophages 36 . Our present results also determined the regulatory role of budesonide and N‐acetylcysteine in the immune function of MP infection.…”
Section: Discussionsupporting
confidence: 66%
“…A large number of medicinal plants have been found to possess medicinal properties against COPD (Mitra et al, 2022). Natural flavonoids, the main active components of numerous medicinal plants, also have been proven to have therapeutic potential in COPD (Fu et al, 2022). Scutellarin, a main active ingredient extracted from Scutellaria baicalensis and Erigeron breviscapus , is a flavonoid with significantly anti‐inflammatory and anti‐cancer activities (Wang & Ma, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of T2DM, polyphenols exhibit multifaceted actions, including improving insulin sensitivity, enhancing pancreatic β-cell function, and ameliorating glucose uptake, collectively contributing to glycemic control and reducing the risk of diabetic complications. Furthermore, polyphenols exert anti-inflammatory effects by suppressing pro-inflammatory cytokines and signaling pathways, thus attenuating chronic low-grade inflammation implicated in the pathogenesis of cardiovascular disease, obesity, T2DM, and various other chronic diseases, as shown in Figure 5 [411][412][413][414][415][416][417][418][419][420][421][422][423][424][425][426][427]. Additionally, polyphenols demonstrate chemo-preventive properties by inhibiting carcinogenesis, modulating cell cycle progression, inducing apoptosis, and suppressing tumor angiogenesis, highlighting their potential in cancer prevention and adjuvant therapy.…”
Section: Polyphenols In Disease Managementmentioning
confidence: 99%
“…Moreover, polyphenols hold promise in neuroprotection by mitigating neuroinflammation, preserving neuronal function, and inhibiting protein misfolding and aggregation, thereby potentially delaying the onset and progression of neurodegenerative diseases such as Alzheimer's and Parkinson's diseases [252,264]. Collectively, the multifaceted bioactivity of polyphenols underscores their therapeutic potential in mitigating the burden of chronic diseases across diverse pathological contexts [411][412][413][414][415][416][417][418][419][420][421][422][423][424][425][426][427].…”
Section: Polyphenols In Disease Managementmentioning
confidence: 99%
See 1 more Smart Citation